Pranutė Aukštikalnytė-Jokimaitienė, One of the “Tragic Generation” - Mitaitė, Donata (Tautosakos darbai, 2023)
This article, a piece on the history of literature, purports surveying all the poetic œuvre by Pranutė Aukštikalnytė-Jokimaitienė (1922–1989), written during comparatively short periods of time, i. e. in 1938–1948 and 1964–1966. Her poetry puts forward ideals of loyalty to one’s native land, as well as states of homelessness and wandering; in her early compositions one can detect certain influence of the neo-romantics, while in the later ones, a somewhat modified folkloric tradition. Her poems employ characters that used to be favored by the Neo-Romanticism and generally are well-known in the global culture, including the madwoman, the king, the traveler, Cain, Ophelia, etc. During the postwar period, P. Aukštikalnytė wrote a handful of syllabotonic poems and a cycle of thirty five vers libres “Skausmo pasakos” (“Tales of Pain”). The latter are fragmented, they emphasize loneliness, homelessness, foreboding of death and willingness to protect the weaker. After editors of the almanac “Poezijos pavasaris” (“Poetry Spring”) in 1966 rejected her poems, the poetess wrote a few more and fell silent ever since. The author of the article concludes that, like other young poets of the time who did not agree to make their talent serve Soviet ideology, P. Aukštikalnytė did not fully employ her poetical powers. One can describe her early poems as very promising, but later she consciously chose another path – that of the folklore researcher, for her, the one and only.